Efficacy of Sinus Tarsal Approach Compared With Conventional L-Shaped Lateral Approach in the Treatment of Calcaneal Fractures: A Meta-Analysis - Ma, Dongmei; Huang, Lei; Liu, Bin; Liu, Zhigang; Xu, Xin; Liu, Jianfeng; Chu, Tianyue; Pan, Liming (Frontiers in Surgery, 2021)
Background The aim of this study is to compare the efficacy of Sinus Tarsal Approach (STA) with that of Conventional L-shaped Lateral Approach (CLSLA) in the treatment of calcaneal fractures by meta-analysis. Methods PubMed, EMbase, Web of Science, CNKI, and China Wanfang database were searched to collect clinical randomized or non-randomized controlled trials of STA and CLSLA in the treatment of calcaneal fractures from January 2010 to May 2020. The data was analyzed by Stata 15.0 software. Results A total of 12 clinical trials were included, all of which were retrospective studies, including 961 patients. The results showed that STA compared with CLSLA, there was no difference in operation time with mean difference (MD)=-5.51（95%CI：-12.57~1.55,P > 0.05）, less bleeding during operation with MD=-18.49（95%CI：-23.79~-13.18）, no difference in Böhler angle after an operation with MD=0.78（95%CI：-0.09~1.65）and in Gissane angle with MD= -0.07（95%CI：-1.90~1.77）, no difference in American Orthopaedic Foot & Ankle Society (AOFAS) score with MD=2.16（95%CI：-1.07~5.38）, higher-excellent and better rate of Maryland food function with relative ratio (RR)=1.12（95%CI：1.04~1.20）, and lower of incidence of postoperative complications with RR=0.23（95%CI：0.14~0.37）. Conclusion STA was more effective than CLSLA in the treatment of calcaneal fractures. Moreover, STA had advantages in terms of less intraoperative bleeding, higher-excellent and better rate of Maryland foot function, lower incidence of postoperative complications and higher safety.